(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores an industrial method for producing molybdenum powders and compact products from copper-molybdenum ore processing waste. The study focuses on efficient recovery techniques using flotation, roasting, and hydrogen reduction. A complete process flow is outlined, including powder formation, compaction, and sintering. The influence of microstructure, sintering parameters, and purification steps is discussed, alongside a literature overview and industrial ap